Pelatihan Kreativitas Siswa Kelas IV di SDN 3 Palangka Melalui Anyaman Kertas Karton - Afna Nadila; Sabariah Sabariah; Istiyati Mahmudah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Developing students' creativity at the elementary school level is an important part of shaping 21st century character and skills. One approach that can be taken is through hand training with cardboard and printed images. This student service activity aims to train the creativity of fourth grade students at SDN 3 Palangka through cardboard weaving training as an innovative learning medium. This activity is motivated by the need for more interesting, active, and enjoyable learning for students. The training is carried out through several stages, namely the compaction of basic weaving techniques, independent practice by students, and evaluation of the work produced. Students are given the freedom to be creative using pieces of used cardboard, with direct guidance from the implementation team and accompanying teachers. The results of the activity show that students are very enthusiastic about participating in this activity. They are able to produce various simple new forms with creative displays that can be used as visual aids in the learning process. In addition to producing work, this activity also forms positive student character such as cooperation, responsibility, perseverance, and courage in displaying work. This activity proves that skills-based training can be a solution to present more lively and meaningful learning. Therefore, this kind of activity is very relevant to be continued and developed as part of a sustainable school program.